Pengaruh Kompetensi terhadap Produktivitas Kerja Karyawan di PT Aroma Wangi Indonesia - Nuniek Dewi Pramanik; Alfazri, Ali (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Examining the relationship between competence and productivity at PT Aroma Wangi Indonesia is the goal of this quantitative research. Thirty workers were selected using a purposive sampling method at random from the respondents inside the organization. We administered tests for normality, linearity, heteroscedasticity, and reliability to our Likert scale surveys, as well as t-tests, reliability analyses, and validity tests, among other statistical procedures, to ensure their data were accurate and reliable. Because the calculated r-value of 9.319 was more than the table r-value of 1.701, with a significance level of 0.000 (< 0.05), the study's findings showed that the independent variable affects the dependent variable. The coefficient of determination test yielded a high R Squared value of 75.6%, lending credence to the hypothesis that competence has a substantial influence on the productivity of PT Aroma Wangi Indonesia personnel. There is a robust relationship between competency and output in the workplace, according to the findings.